Development of Think-Pair-Share (Tps) Model Based Learning Tools for Global Warming Materials - Shinta Bella; Azhar Azhar (Journal of Education and Learning Research, 2023)
The aim of this research is to develope are cooperative model-based learning tools of TPS type with Quizizz learning media on global warming materials for high school XI students. The materials are consisting of Learning Implementation Plan (RPP), Student Worksheet (LKPD), and Learning Outcome Test. This type of research is Research and Development (R&D) with 4D model design. The research instruments used are rpp validation assessment sheets, LKPD, and Learning Results Tests used by validators to assess learning devices. The data analysis in this study uses descriptive analysis, by calculating the validity score of each learning device indicator. Based on the results of the analysis of validity data, the Learning Implementation Plan (RPP) gets an average score of 3.07 (high), the Student Worksheet (LKPD) gets an average score of 3.16 (high) and the Learning Results Test gets an average score of 3.13 (high). Thus, tps-type cooperative model-based learning devices with Quizizz learning media are declared valid and feasible for use in global warming materials in grade XI SMA.